Care for the seafarers: A review of mental health in Austronesia. (7th March 2013) - Guerrero, Anthony P.S.; Fung, Daniel; Suaalii‐Sauni, Tamasailau; Wiguna, Tjhin
Abstract Introduction Continent‐based regional reviews of mental health may not fully describe the status of ethnocultural groups that are widely dispersed across multiple continents or traditional world regions. Our aim was to describe the Austronesians, an ethno‐linguistic group living primarily in islands and coastal areas in the Pacific and Indian Oceans and Southeast Asia. Methods Consulting lay databases, we created matrices to describe the demographic, political, and socioeconomic profiles of nations with majority and minority indigenous Austronesian language‐speaking populations. We then accessed the scientific literature to describe examples of mental health disparities and/or challenges in mental health care delivery. Results Many Austronesian‐speaking people have experienced recent or current foreign occupation, lack of recognized sovereignty, poverty and low socioeconomic status, and low availability of psychiatric resources and providers. An analysis of the biological, psychological/psychocultural, and social and environmental impacts (risk or protective) on either the prevalence/presentation of mental illness, help‐seeking behavior or access to mental health care, or management of mental illness suggested that there may be relatively unique stressors (e.g. loss of homeland from either global warming or nuclear contamination) affecting people in this region and certain biological profiles (e.g. susceptibility to obesity and metabolic syndrome) that may impact psychiatric treatment. Discussion Solutions to mental health challenges in this world region may include culturally relevant and integrative mental healthcare delivery models; resource preserving, prevention‐focused universal mental healthcare; and technology to improve connectivity and increase access to either direct services or workforce‐building education and training.